Jayapura City Development, Plastic Waste, and Enggros Village Community: A Green Theory Perspective - Ellysabeth Surat Lelan; Kustanti Hariwati Dalle (Cenderawasih University, 2021)
This article aims to examine the impact of plastic waste and the expansion of Jayapura city on the people of Enggros village from a green theory perspective. This perspective, which is often considered one of the counter standpoints in international relations, puts forward an environmentally-grounded perspective from the traditional focus on humans. This study adopted descriptive-qualitative analysis as well as library research methods to collect data. Several findings are summarized: 1) the problem of plastic waste in Enggros village is an environmental crisis that needs to be addressed because it has an impact on the decline in fish populations, difficulty accessing clean water, and contamination of mangrove forests; 2) development in the context of modernization in Jayapura city should prioritize the environmental aspects of sustainable development; 3) cooperation from various stakeholders is required – both state and non-state actors – in overcoming the environmental crisis in Enggros village; 4) strengthening the capacity of the indigenous Enggros is required, considering them as important stewards who will protect their environment in the future.KEYWORDSEnggros; Green Theory; Jayapura; Plastic